Students' Perceptions on Using Vocabulary Journal for Mastering Vocabulary: A Descriptive Study at SMAN 12 Padang - Mutiara Cinta Rahmadillah; Sitti Fatimah (Journal of English Language Teaching, 2023)
This study aimed to examine students’ perceptions on using vocabulary journal for mastering vocabulary. There were five aspects investigated, namely the attractiveness, effectiveness, relevance, perceived motivation, and vocabulary aspects. The participants were 65 students of grade XII at Science Program SMAN 12 Padang to whom a questionnaire was given. The data of this research were analyzed using descriptive quantitative method. The results from questionnaire revealed that students had relatively positive perceptions on the use of vocabulary journal for mastering vocabulary. This is shown by the average mean of the questionnaire responses, it was 3.03 out of 4.00. Thus, the findings show that the majority of the students viewed that learning new vocabulary using vocabulary journal was fun and could help them retain the new vocabulary they have learned. Students thought that vocabulary journal is so appropriate to be used in English class and motivated them in learning new words. Most of the students also felt that vocabulary journal helps them in comprehending the use of a certain words and spell the words correctly. It can be inferred that the use of vocabulary journal for vocabulary learning is attractive, effective, relevance, perceived motivation, and promote all the vocabulary aspects.